THE BARRENNESS OF MODERN HUMAN SPIRITUALITY IN THE SEYYED HOSSEIN NASR'S PERSPECTIVE - Kasmuri Selamat; Ananda Rezki Saputra; Zainal Fadri; Zaidi Hajazi (Alfuad: Jurnal Sosial Keagamaan, 2022)
Modern humans are human beings who are slaves to material things, are materialistic, hedonistic and want to overpower all aspects of life. Modern humans are also humans who deny the voice of conscience and the call of human nature. As a result, they suffer from multidimensional diseases such as excessive anxiety, life feels meaningless, suffers from isolation from themselves, from their social environment and from their God. To save such a situation, an Islamic intellectual figure, Seyyed Hosein Nasr, offers the concept of a perfect human being Islamically by returning to the nature that has been bestowed by Allah, namely integrating the three elements that have been possessed, body, mind and soul.